Analisis Rancangan Perbaikan Desain Robot Rehabilitasi Pascastroke Anggota Gerak Atas Dengan Integrasi Metode Qfd Dan Dfma - SUWARDI, Acep ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The occurrence of limb immobilization due to residual symptoms caused by a decline in brain function after stroke, could have a negative impact if no further medical treatment. Physiotherapist alternative healing methods into existing solutions to address the symptoms of a stroke, paralysis, and healing poststroke recovery. These methods are categorized in the healing process Continues Active Movement (CAM) because of the direct involvement between stroke patients and physiotherapists. Together with the development of technology, other methods that can be taken in a cost efficient manner is the use of robotic-based assistive rehabilitation. This method is included in the category of the healing process Continues Passive Movement (CPM) in which patients in treatment by a tool that can perform a variety of movements rehabilitation accordance with a program that has been in the right input. Based on these considerations form the basis for attempts to develop an innovation in developing tools for stroke patients. Making this tool design starts with analyzing the preliminary design proposals that have been developed previously. The purpose of this research is to simplify a concept design of the product to obtain concept design a product more efficient both in the manufacturing and assembly process with used of the Design For Manufacture and Assembly (DFMA). DFMA methods in the process of reviewing the overall plan in getting a new design such as bills of materials, assembly charts, route sheets, operational processes charts to obtain a new design that costs more than the minimum cost design of the initial design of the product. In addition, in this study DFMA method integrating the method of Quality Function Deployment (QFD), which aims to get the maximum draft is not just a reduction in manufacturing cost aspect. However, the results of product design can appropriately meet the needs and desires of customers (customer satisfaction). The results of the analysis showed a reduction in the cost and time of production where production costs are initially equal to IDR. 4.559.468,95 to be IDR. 3.805.720,00 as well as the first production time takes 2 days 2 hours 9.6 minutes to 1 days 9 hours in the manufacturing and assembly process.